Methodological basis for systematic analysis of military soil degradation - Popsuy, A. O. (Man and Environment. Issues of Neoecology, 2025)
Purpose. To substantiate the methodological foundations of the systematic analysis of degradation processes in soils of military origin and to form an integrated model for assessing their condition, dynamics and forecasting restoration. The scientific need for the creation of an interdisciplinary monitoring system combining geochemical, physical-mechanical, microbiological and landscape-analytical approaches is identified. Methods. Mathematical modeling, statistical analysis and machine learning systems were used to process and generalize data, which provided a comprehensive assessment of the impact of military factors on the condition of soils. Results. The study used system-ecological and geoinformation approaches, methods of toxicological analysis, remote sensing, as well as index assessment of degradation processes using integral indicators - the index of ecological soil degradation (IEDS), the index of structural-biological stability (ISBS) and the coefficient of military-technogenic load (WTC). It has been proven that the degradation of soils of military origin has a cascading nature: primary mechanical damage causes secondary processes - compaction, erosion, reduced water permeability, loss of microbiological activity and structural stability. According to the results of the analysis, it was established that in areas of active hostilities, the concentrations of toxic elements exceed the maximum permissible values by 5–12 times, and microbiological activity decreases by 35–65%. The developed system model allows identifying territories with the highest level of degradation, predicting further changes in the state of soils and forming priorities for reclamation. The combination of GIS mapping, bioindication and analytical modeling creates a scientific basis for ecological and management decisions in the field of post-conflict recovery. Conclusions. The proposed methodological scheme of system analysis is an effective tool for assessing degradation processes in soils of military origin. It provides integration of multi-level environmental data, contributes to the formation of adaptive reclamation strategies and increases the efficiency of state environmental monitoring. The use of such a system will minimize social and environmental risks, preserve agricultural landscapes and support sustainable development of affected areas.